2010
DOI: 10.1007/s10144-010-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Historical demography of a wild lemur population (Propithecus verreauxi) in southwest Madagascar

Abstract: The human colonization of Madagascar is associated with the extinction of numerous lemur species. However, the degree to which humans have negatively influenced the historical population dynamics of extant lemur species is not well understood. This study employs genetic and demographic analyses to estimate demographic parameters relating to the historical population dynamics of a wild lemur population, Verreaux's sifaka (Propithecus verreauxi). The genetic analyses are used to determine whether this population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 70 publications
(93 reference statements)
2
11
0
Order By: Relevance
“…Whether or not the initial population decline was caused by the onset of the LGM, and whether or not there was a population expansion in the Early Holocene, it is clear that environmental conditions in the Mid‐Late Holocene have had a dramatic effect on drill population dynamics and modern drill genetic diversity. Although some studies identified recent (i.e., the past few hundred years) habitat changes by humans as the main source of past population size change and current genetic variation in tropical mammals (Goossens et al 2006; Olivieri et al 2008; Craul et al 2009; Thalmann et al 2011), other studies are consistent with our conclusion that Mid‐Late Holocene events were particularly influential (Heller et al 2008; Okello et al 2008; Lawler 2011). This time period saw an increase in aridity and the opening up of forests across Africa.…”
Section: Discussionsupporting
confidence: 89%
“…Whether or not the initial population decline was caused by the onset of the LGM, and whether or not there was a population expansion in the Early Holocene, it is clear that environmental conditions in the Mid‐Late Holocene have had a dramatic effect on drill population dynamics and modern drill genetic diversity. Although some studies identified recent (i.e., the past few hundred years) habitat changes by humans as the main source of past population size change and current genetic variation in tropical mammals (Goossens et al 2006; Olivieri et al 2008; Craul et al 2009; Thalmann et al 2011), other studies are consistent with our conclusion that Mid‐Late Holocene events were particularly influential (Heller et al 2008; Okello et al 2008; Lawler 2011). This time period saw an increase in aridity and the opening up of forests across Africa.…”
Section: Discussionsupporting
confidence: 89%
“…(44)] from the northwest of Madagascar, where habitat loss has been massive in the past century (32). Similarly Lawler (80) concluded that P. verreauxi also suffered from a bottleneck less than 2,000 y ago in the southwest of Madagascar, again, a region where human impact and deforestation are more serious than in Daraina (14). Similar results have also been suggested for other primates [orangutans (81) and howler monkeys (82)].…”
Section: Resultssupporting
confidence: 64%
“…The LTRE analysis performed on the Cayo Santiago population shows that most of the variation in population growth rate over the past 28 years is due to variation in life cycle transitions of young adult and adult females. Therefore, in order to understand the temporal dynamics of λ, it is necessary to identify processes that influence these two life cycle stages [Lawler, 2011b]. Young adults (three-yr-olds) in Cayo Santiago represent a stage of potential sexual maturation.…”
Section: Discussionmentioning
confidence: 99%
“…A life table response experiment (LTRE) of random design [Caswell 2000; Lawler, 2011b] was performed to quantify the population-level effect of variation in vital rates across different levels of adult density. The LTRE is a retrospective analysis that determines how variation in life-cycle transitions, during a sequence of years, contributed to the observed variation in the population growth rate [Caswell 2000; 2001].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation